2016
DOI: 10.1021/jacs.6b05436
|View full text |Cite
|
Sign up to set email alerts
|

Additive- and Metal-Free, Predictably 1,2- and 1,3-Regioselective, Photoinduced Dual C–H/C–X Borylation of Haloarenes

Abstract: We report herein a simple, additive- and metal-free, photoinduced, dual C–H/C–X-borylation of chloro-, bromo-, and iodoarenes. The reaction produces 1,2- and 1,3-diborylarenes on gram scales under batch and continuous flow conditions. The regioselectivity of the dual C–H/C–X-borylation is determined by the solvent and the substituents in the parent haloarenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 81 publications
0
47
0
Order By: Relevance
“…[6] However,a ll these valuable methods require at ransition metal catalyst, al igand and as toichiometric amount of ab ase.T oo ur knowledge,m etal and additive-free radical borylation of alkyl halides with diborons is unknown. [7] Arylboronates can be obtained from haloarenes and diborons via reactive aryl radicals [8][9][10][11][12][13] (Scheme 1B). Along these lines,Marder developed azinc(II)-catalyzed borylation of aryl halides using astoichiometric base [8] and photoinduced aryl halide borylation was reported by Larionov, [9] Li [10] and Fu.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] However,a ll these valuable methods require at ransition metal catalyst, al igand and as toichiometric amount of ab ase.T oo ur knowledge,m etal and additive-free radical borylation of alkyl halides with diborons is unknown. [7] Arylboronates can be obtained from haloarenes and diborons via reactive aryl radicals [8][9][10][11][12][13] (Scheme 1B). Along these lines,Marder developed azinc(II)-catalyzed borylation of aryl halides using astoichiometric base [8] and photoinduced aryl halide borylation was reported by Larionov, [9] Li [10] and Fu.…”
mentioning
confidence: 99%
“…[7] Arylboronates can be obtained from haloarenes and diborons via reactive aryl radicals [8][9][10][11][12][13] (Scheme 1B). Along these lines,Marder developed azinc(II)-catalyzed borylation of aryl halides using astoichiometric base [8] and photoinduced aryl halide borylation was reported by Larionov, [9] Li [10] and Fu. [11] Recently,apyridine-catalyzed radical borylation of aryl halides was disclosed by Jiao.…”
mentioning
confidence: 99%
“…A similar photoinduced borylation method was also developed by Li 30,31 . We also showed that a 1,2- and 1,3-regioselective dual C–H/C–X borylation of haloarenes can be achieved on preparative scale 32 (Fig. 1d).…”
Section: Introductionmentioning
confidence: 61%
“…In 2016, Larionov and co‐workers developed an unprecedented photoinduced dual C–H/C−X borylation of haloarenes 152 with B 2 Pin 2 as the borylation source under mild conditions (Scheme ) . A variety of 1,2‐ ( 153 ) and 1,3‐ ( 154 ) diborylarenes have been achieved regioselectively in good to excellent yields from chloro‐, bromo‐, and iodo‐arenes.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…In 2016, Larionov and co-workers developed an unprecedented photoinduced dual C-H/CÀ X borylation of haloarenes 152 with B 2 Pin 2 as the borylation source under mild conditions (Scheme 46). [74] A variety of 1,2-(153) and 1,3-Scheme 43. Knoevenagel-type reaction involved annulation to access tetrasubstituted thiophenes.…”
Section: Photoinduced Borylation Reactionsmentioning
confidence: 99%